Rekonstruksi Lahan Idle yang Terintrusi Air Laut Menjadi Areal Sawah-Tambak - Sahabuddin Sahabuddin; Early Septiningsih; H S Suwoyo; Agus Nawang; Agus Cahyadi (Jurnal Ilmu Alam dan Lingkungan, 2020)
Many farmers' farmlands are found to be unproductive according to their owner's wishes. The condition is sometimes left even abandoned by the owner because it does not produce economic value for the welfare of the fishermen farming community. Touch of technology is expected to change the condition of the land from idle to helpless. Therefore, a study and constructive approach was carried out in the form of reconstruction of idle land that was intrused by seawater belonging to farmer groups in the form of reconstruction of idle land into paddy fields and ponds so that it was suitable for cultivation. This activity was carried out in Oring Lawallu Village, Soppeng Riaja Barru District of South Sulawesi. The study began with a site survey, socialization and land reconstruction from an idle paddy field to paddy fields for rice and caren for shrimp farming. The area of land used is seawater intrusion land of about 1 ha, which is owned by 5 members of the Massiddie farmer group, then reconstructed using an excavator owned by the Dinas Perikanan District of Barru. The results of the land reconstruction activities consisted of 0.363 ha of land area and caren land of around 0.242 ha equipped with 0.092 ha of reservoir and the rest of the canal and dike separating between paddy fields / ponds. The lands that have been reconstructed are suitable to be used as land for cultivation of rice and tiger shrimp and other aquaculture commodities